Population structure and productivity of Whistling Swans on the Yukon Delta, Alaska - Lensink, Calvin J (Wildfowl, 1973)
Observations of Whistling Swans from low flying aircraft on the Yukon Delta, Alaska, provide records which permit analysis of annual variations in productivity. Climatic conditions of early spring are the most important factor affecting production, a late spring resulting in a reduced number of nests and reduced clutch size. The percentage of territorial pairs with broods has varied from about 15 to 50%. The average number of cygnets in broods at time of fledging has varied from 2?52 to 3?63.